Frege e a teoria da verdade como identidade - Giarolo, Kariel Antonio (2011)
The main objective of this work consists in investigating the relationship between Frege s conception of truth and the so called Identity Theory of Truth . An identity theory of truth is described in literature as the thesis sustaining that truth consists, fundamentally, in the identity between the content of a judgment or proposition and a fact. The proposition expressed by a sentence, as in Aristotle was a disciple of Plato , is true if, and only if, it is a fact that Aristotle was a disciple of Plato. Thus, the contents of the sentences would be in a relation of identity towards the facts, and would not be in a relation of correspondence, as classic theories of truth sustain. In Der Gedanke, published in 1918, Frege seems to sustain this theory, even though his conception of truth is much larger than that. On the article, he explicitly affirms that a fact is a thought that is true. Such affirmation fits perfectly in the identity theory of truth s slogan. Nevertheless, there s plenty of discussion on the subject in secondary literature. Authors such as Baldwin, Dodd, Kemp, Horsnby and Sluga have discussed the identification between facts and true thoughts, and have given explanations that are sometimes rather antagonistic. That is why it is of great value the reconstruction and the discussion of such interpretations, in the attempt to clarify Frege s purpose on the referred affirmation. Along with that, it is necessary to review other aspects of Frege s philosophy, since his conception of truth in general, and, particularly, the identity theory of truth, are connected to the whole of his philosophy.